Analysis of the Impact of Solar Radiation on the Battery Charging Duration and Operation of a DC Solar-Powered Water Pump - Bakti Indra Kurniawan; Mohammad Noor Hidayat; Priya Surya Harijanto; Ananda Setyo Abimanyu; Naufaliawan Abraham (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2025)
This research examines the effect of solar irradiance on the performance of a solar-powered water pump (SWP). The primary objective is to determine how solar irradiance affects battery charging time and pump operational duration. Using a system consisting of a solar panel, a battery, and a pump in the Malang region, we collected data on both sunny and cloudy days. The results indicate that solar irradiance is a crucial determinant of the system's efficiency. On sunny days, battery charging is faster, and the pump can operate for a longer period. Conversely, on cloudy days, battery charging slows down, and the pump's duration becomes shorter. This study concludes that solar irradiance is a key factor in optimizing SWP systems, and the use of a battery is essential to ensure stable operation.